TINJAUAN LITERATUR TENTANG SISTEM EKONOMI DAN DAMPAKNYA TERHADAP STABILITAS KEUANGAN: FOKUS PADA INFLASI DAN HUTANG - Affandy Agusman Aris; Loso Judijanto; Darmun; Triani patra pertiwi; Muhammad Hendra (LPPM Universitas Ekasakti, 2024)
This study aims to explore how the economic system, through the mechanisms of inflation and debt, can impact financial stability, focusing on the interaction between inflation, debt, and financial stability. This research is a literature review concentrating on both theoretical and empirical analyses of the relationship between the economic system, specifically inflation and debt factors, and financial stability. The results show that financial stability is a condition where the financial system including institutions, markets, and infrastructure functions optimally and can absorb economic shocks without significantly disrupting economic activity. This stability supports efficient resource allocation, economic growth, and investor confidence, with the capacity to manage risks effectively. However, financial stability can be disrupted by uncontrolled inflation, excessive debt, and imbalances in the economic system. High inflation can erode purchasing power and increase borrowing costs, while excessive debt raises the risk of default and slows economic growth. The interaction between inflation and debt complicates financial stability, as high inflation may reduce the real value of debt but also increase borrowing costs. Global financial crises, such as the 2007-2008 Financial Crisis, the European Debt Crisis, and the 2021-2023 Energy Crisis, underscore the need for effective policies in managing inflation and debt to maintain financial stability and support sustainable economic growth.